(untitled) (ACME, 2020)
This paper aims to investigate the Latin origins of the agricultural metaphor of writing, made famous by the Veronese Riddle in particular. The linguistic and conceptual features of the metaphor and its evolution in relation to the various writing supports will be analysed through a parallel and diachronic examination of literary and epigraphic sources, from the third century B.C. up to the threshold of the Middle Ages. The first part concerns the peculiarities of the metaphor in the enigmatic production of the medieval era, whose roots are sought within ancient literature. The analysis then focuses on a number of fundamental terms used to express the association between ploughing and writing in archaic and classical Latin, such as arare, perarare, inarare and, above all, exarare. This emphasises the role of mediation exercised by Christian literature, which has left an extremely rich and varied metaphorical complex to the imaginative mind of medieval man, at the basis of a literary and popular tradition that has survived to this date. The second part deals with the epigraphic sources which, albeit quantitatively lower than the literary ones, are able to enrich the evolutionary framework of the metaphor. In particular, the two epigraphs taken into consideration allow us to focus on the figurative use of the verb sulcare and its derivative desulcare. While this was not attested for the agricultural metaphor of writing before the first century A.D., they will be considered and reformulated in Christian literary production only starting from the fourth century A.D.